Gallium nitride devices for power electronic applications - Baliga, B Jayant (Semiconductor science and technology, 2013)
Recent success with the fabrication of high-performance GaN-on-Si high-voltage HFETs has made this technology a contender for power electronic applications. This paper discusses the properties of GaN that make it an attractive alternative to established silicon and emerging SiC power devices. Progress in development of vertical power devices from bulk GaN is reviewed followed by analysis of the prospects for GaN-on-Si HFET structures. Challenges and innovative solutions to creating enhancement-mode power switches are reviewed.